1-Hour OGTT Plasma Glucose as a Marker of Progressive Deterioration of Insulin Secretion and Action in Pregnant Women - Alessandra Ghio; Giuseppe Seghieri; Cristina Lencioni; Roberto Anichini; Alessandra Bertolotto; Alessandra De Bellis; Veronica Resi; Emilia Lacaria; Stefano Del Prato; Graziano Di Cianni (International Journal of Endocrinology)
Considering old GDM diagnostic criteria, alterations in insulin secretion and action are present in women with GDM as well as in women with one abnormal value (OAV) during OGTT. Our aim is to assess if changes in insulin action and secretion during pregnancy are related to 1-hour plasma glucose concentration during OGTT. We evaluated 3 h/100 g OGTT in 4,053 pregnant women, dividing our population on the basis of 20 mg/dL increment of plasma glucose concentration at 1 h OGTT generating 5 groups (<120 mg/dL, 𝑛=661; 120–139 mg/dL, 𝑛=710; 140–159 mg/dL, 𝑛=912; 160–179 mg/dL, 𝑛=885; and ≥180 mg/dL, 𝑛=996). We calculated incremental area under glucose (AUCgluc) and insulin curves (AUCins), indexes of insulin secretion (HOMA-B), and insulin sensitivity (HOMA-R), AUCins/AUCgluc. AUCgluc and AUCins progressively increased according to 1-hour plasma glucose concentrations (both 𝑃<0.0001 for trend). HOMA-B progressively declined (𝑃<0.001), and HOMA-R progressively increased across the five groups. AUCins/AUCgluc decreased in a linear manner across the 5 groups (𝑃<0.001). Analysing the groups with 1-hour value <180 mg/dL, defects in insulin secretion (HOMA-B: −29.7%) and sensitivity (HOMA-R: +15%) indexes were still apparent (all 𝑃<0.001). Progressive increase in 1-hour OGTT is associated with deterioration of glucose tolerance and alterations in indexes of insulin action and secretion.